Hepatic encephalopathy increases the risk for mortality and hospital readmission in decompensated cirrhotic patients: a prospective multicenter study - Riggio, Oliviero; Celsa, Ciro; Calvaruso, Vincenza; Merli, Manuela; Caraceni, Paolo; Montagnese, Sara; Mora, Vincenzina; Milana, Martina; Saracco, Giorgio Maria; Raimondo, Giovanni; Benedetti, Antonio; Burra, Patrizia; et al. (Frontiers in Medicine, 2023)
Introduction:Hepatic encephalopathy(HE) affects survival and quality of life of patients with cirrhosis. However, longitudinal data on the clinical course after hospitalization for HE are lacking. The aim was to estimate mortality and risk for hospital readmission of cirrhotic patients hospitalized for HE. Methods:We prospectively enrolled 112 consecutive cirrhotic patients hospitalized for HE(HE group) at 25 Italian referral centres. A cohort of 256 patients hospitalized for decompensated cirrhosis without HE served as controls(No HE group). After hospitalization for HE, patients were followed-up for 12 months until death or liver transplant(LT). Results:During follow-up, 34 patients(30.4%) died and 15 patients(13.4%) underwent LT in HE group, while 60 patients(23.4%) died and 50 patients(19.5%) underwent LT in No HE group. In the whole cohort, age(HR 1.03, 95%CI 1.01-1.06), HE(HR 1.67, 95%CI 1.08-2.56), ascites(HR 2.56, 95%CI 1.55-4.23) and sodium levels(HR 0.94, 95%CI 0.90-0.99) were significant risk factors for mortality. In HE group, ascites(HR 5.07, 95%CI 1.39-18.49) and BMI(HR 0.86, 95%CI 0.75-0.98) were risk factors for mortality and HE recurrence was the first cause of hospital readmission. Conclusions:In patients hospitalized for decompensated cirrhosis, HE is an independent risk factor for mortality and the most common cause of hospital readmission compared to other decompensation events. Patients hospitalized for HE should be evaluated as candidates for LT.